2020
DOI: 10.1007/s10482-020-01393-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome rearrangements and megaplasmid loss in the filamentous bacterium Kitasatospora viridifaciens are associated with protoplast formation and regeneration

Abstract: Filamentous Actinobacteria are multicellular bacteria with linear replicons. Kitasatospora viridifaciens DSM 40239 contains a linear 7.8 Mb chromosome and an autonomously replicating plasmid KVP1 of 1.7 Mb. Here we show that lysozymeinduced protoplast formation of the multinucleated mycelium of K. viridifaciens drives morphological diversity. Characterisation and sequencing of an individual revertant colony that had lost the ability to differentiate revealed that the strain had not only lost most of KVP1 but a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Furthermore, we cannot exclude the possibility that more than one genome could have been embedded in some protoplasts, thus generating clones with a mixed genetic background. Neither we can rule out that physiological or genetic changes occurring during protoplast formation and regeneration [ 33 ] might have concurred, at least for some clones, in determining the differences observed in teicoplanin productivity and complex profile, or in growth pattern. However, what is clear from our study is that integrating strain improvement and strain maintenance approaches with the use of protoplasts can be a successful strategy for unravelling the hidden industrial potential of A. teichomyceticus and related multinucleated “rare” actinomycetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we cannot exclude the possibility that more than one genome could have been embedded in some protoplasts, thus generating clones with a mixed genetic background. Neither we can rule out that physiological or genetic changes occurring during protoplast formation and regeneration [ 33 ] might have concurred, at least for some clones, in determining the differences observed in teicoplanin productivity and complex profile, or in growth pattern. However, what is clear from our study is that integrating strain improvement and strain maintenance approaches with the use of protoplasts can be a successful strategy for unravelling the hidden industrial potential of A. teichomyceticus and related multinucleated “rare” actinomycetes.…”
Section: Discussionmentioning
confidence: 99%
“…The delegation of the production of antibiotics to a “sterile caste” (non-spore producing) of the microbial population reduces the overall costs of biosynthesis, maximizes the magnitude and diversity of the produced antibiotics and increases the reproduction efficiency of the “non-sterile caste” (spore producing) [ 8 ]. The process that predisposes to the division of labor is based on differential gene expression [ 29 ] and on genomic instability, the latter creating phenotypically heterogeneous subpopulations of cells, mainly by means of large and irreversible deletions or amplifications at the chromosomal termini [ 8 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…When bacteria were subjected to growth stress or when the plasmid stability determinants were missing, genetic changes of the plasmids could possibly occur ( Bardaji et al . 2019 ; Ramijan et al . 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The following genome sequence alignment method for determining genome deletion in the mutants was essentially based on previous studies ( Bardaji et al . 2019 ; Ramijan et al . 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Charusanti and co-workers found that loss of pSCL4 following several rounds of selective pressure by co-culture with Staphylococcus aureus was likely responsible for the activation of holomycin production [ 48 ]. Alvarez-Alvarez and co-workers constructed a pSCL4-cured type strain derivative by deleting parA-parB using PCR-targeting [ 47 ], and the same group also cured pSCL4 from an oppA2 -deleted mutant by protoplast regeneration [ 47 ] (the same technique reported for Streptomyces rochei [ 55 ]), a technique demonstrated to lead to unpredictable genetic rearrangements and loss of sequence [ 56 ]. Unfortunately, while the data available for these mutants indicates significant loss of sequence and rearrangements near the chromosome termini, they do not allow their topology to be determined.…”
Section: Discussionmentioning
confidence: 99%